Fatores prognósticos na insuficiência cardíaca chagásica com disfunção ventricular grave - Costa , Sandra de Araújo (2016)
Introduction: Heart failure represents a complex clinic syndrome in which several mechanisms are involved. Patient’s prognosis is bad and Chagas disease, between other etiologies, has the worse prognosis in heart failure. There are some controversies in relation to many factors that possibly identify the patients with especially high risk of death in heart failure. Although more than 40 variables have been identified as prognostic predictors in HF, there is no consensus about its applicability in clinical practice. Objectives: Identify the association between clinical and laboratory factors in chagasic heart failure with severe ventricular disfunction; analyze the association between prognostic factors and mortality rate; examine the global survival of this population in a 7 years and 6 months follow up. Methods: The present study is a cutting of the “Randomized, Multicenter Celular Therapy in Cardiopathies - Chagas Cardiopathy”, with retrospective analysis of the data collected prospectively. The following variables were analyzed: age, arterial pressure (AP) ejection fraction (EF), plasmatic sodium, creatinina, 6 minutes walking test (6MWT), nonsustained ventricular tachycardia (NSVT), electrocardiogram QRS width, echocardiogram indexed left atrium volume (iLAV) and functional class. Results: From the 60 participants, 53 (88,3%) died during the total follow up period (90 months) and 7 (11.7%) remained alive until the end of the period. The general accumulated survival probability of the severe Chagas etiology patients, identified in our study, was about 11%. The systolic arterial pressure did not correlate in a significant manner to the mortality outcome, although the increasing in 10 mmHg in systolic arterial pressure resulted in a reduction of 4% in the risk of death. There was no statistical significance to the variables age, ejection fraction, 6MWT and QRS width in relation to the outcome mortality. There was statistical significance in relation to plasmatic sodium and creatinina, with the outcome mortality, in the univariate analyses. However, after adjust to the multivariate analyses model, they lost significance. From the variables used in the Cox regression model, only NSVT and the indexed atrium volume remained as independent mortality predictors. Unsustained ventricular thachycardia presented a significant risk value – HR = 2,11 (95% CI, 1,04 – 4,31) p<0,05. iLAV values >72 ml/m2 were associated to a significant risk in mortality – HR = 3,51 (95% CI, 1,63 – 7,52), p<0,05. Conclusions: In Chagas etiology heart failure patients, with important ventricular function commitment, the presence of Holter NSVT and the iLAV > 72mL/m2 gives them a worse prognosis. This population prognosis is bad, with a cumulated survival probability of only 11% in 7.5 years.